Early Prediction of Nonresponders to Treatment with Interferon Alpha-2B and Ribavirin in Patients with Chronic Hepatitis C. (1st August 2003) - Liu, Louis WC; Tomlinson, George; Mazzulli, Tony; Murray, Alison; Heathcote, Jenny
Abstract : BACKGROUND: Treatment of chronic hepatitis C virus (HCV) infection with interferon alpha-2b and ribavirin is costly in terms of side effects, medical resources and drug costs. Furthermore, less than 50% of patients overall have a sustained virological response (SVR). OBJECTIVE: To determine if the log fall in HCV RNA between baseline and week 1 (b-wk1) and between baseline and week 4 (b-wk4) after starting treatment could identify the nonresponders. PATIENTS AND METHODS: Sixty-three patients who had completed a full course of therapy were identified. Quantitative measurements of HCV RNA were analyzed from stored sera, collected prospectively. RESULTS: SVR was achieved in 47.1% and 47.3% of patients in the b-wk1 and b-wk4 groups, respectively. No patients had an SVR with a fall in HCV RNA of less than 0.35 log10 and 1.05 log10 at week 1 and week 4, respectively. This accounted for 44.4% and 51.7% of the nonresponders in the b-wk1 and b-wk4 groups, respectively. Once the decline in viral load was known, genotype, age, sex and baseline viral load did not provide additional power in predicting treatment responses. CONCLUSION: A fall of 1.05 log10 in HCV RNA at week 4 predicts those patients who will not respond, identifying one-half of all nonresponders; this allows therapy to be stopped early, without depriving any patient who would have an SVR from treatment.